Sodium-ion battery negative electrode material, preparation method thereof and sodium-ion battery
By crosslinking and carbonizing the oxidized asphalt with a hydroxyl-rich hard carbon precursor, the sodium ion battery negative electrode material is prepared, which solves the shortcomings of existing materials in terms of energy density, cycle life and conductivity, and achieves higher specific capacity, rate performance and stability.
Patent Information
- Application Number
- CN202411568402.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-02-14
AI Technical Summary
The existing sodium ion battery anode materials have shortcomings in energy density, cycle life and electrical conductivity, especially the limited cross-linking effect of soft carbon and hard carbon, which affects the improvement of electrochemical performance.
By mixing, crosslinking and carbonizing the hydroxyl-rich hard carbon precursor with oxidized asphalt, the sodium ion battery negative electrode material is prepared, which significantly improves the crosslinking degree between soft and hard carbon precursors.
Significantly improves the sodium storage performance of the negative electrode material, improves specific capacity and first-time Coulomb efficiency, enhances conductivity and rate performance, and extends service life. It is suitable for fast charging and high-power applications.
Smart Images

Figure CN119430133A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery negative electrode materials, and in particular to a sodium ion battery negative electrode material and a preparation method thereof, and a sodium ion battery. Background Art
[0002] With the rapid development of renewable energy and the growing market of electric vehicles, the demand for innovation in battery technology has become more urgent. As an alternative to lithium-ion batteries, sodium-ion batteries have attracted more and more attention due to their abundant resources, low cost and environmental friendliness. The main challenge of sodium-ion batteries lies in the performance of electrode materials, especially the energy density, cycle life and conductivity of negative electrode materials.
[0003] At present, the negative electrode materials of sodium ion batteries mainly include carbon-based materials, metal oxides and alloys. Among them, carbon-based materials have become the focus of research due to their good conductivity, chemical stability and relatively low cost. Hard carbon, due to its large interlayer spacing and disordered structure, is conducive to the deintercalation of sodium ions and exhibits a higher specific capacity, but the low carbon yield and initial coulombic efficiency increase the cost and limit its application. In contrast, soft carbon derived from asphalt has a higher degree of order and excellent conductivity, but due to its small interlayer spacing, the deintercalation ability of sodium ions is weak, resulting in low sodium storage capacity. In order to solve the above problems, the strategy of using composite materials of soft carbon and hard carbon has gradually attracted attention. This composite material can combine the high capacity of hard carbon with the good rate performance of soft carbon, significantly improving the overall performance of sodium ion batteries. The key to the design of composite materials is that the combination of soft carbon and hard carbon can enhance the sodium storage capacity of the battery, thereby improving the specific capacity; the composite material can improve the stability of the battery during charging and discharging and extend its service life.
[0004] Current research shows that using asphalt as a soft carbon source and directly mixing it with hard carbon precursors such as phenolic resin, polyacrylonitrile (PAN), starch, etc. for pyrolysis can improve the reversible capacity and rate performance of sodium ion battery negative electrode materials to a certain extent. This method promotes the interaction between soft carbon and hard carbon by adjusting the ratio of precursors and pyrolysis conditions, thereby improving the electrochemical properties of the material. However, when asphalt and hard carbon precursors are directly pyrolyzed, the cross-linking effect between the two is limited, and the structural regulation advantages of soft carbon / hard carbon negative electrode materials cannot be fully utilized, thus affecting the improvement of their electrochemical performance.
[0005] In view of this, it is necessary to design an improved sodium ion battery negative electrode material and a preparation method thereof and a sodium ion battery to solve the above problems. Summary of the invention
[0006] The object of the present invention is to provide a sodium ion battery negative electrode material and a preparation method thereof and a sodium ion battery, wherein the method comprises mixing, crosslinking and carbonizing a hydroxyl-rich hard carbon precursor with an oxidized asphalt to prepare the sodium ion battery negative electrode material. Through this method, the degree of crosslinking between the soft and hard carbon precursors can be effectively improved, and their respective structural advantages can be fully utilized, thereby significantly improving the sodium storage performance of the negative electrode material.
[0007] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:
[0008] S1. preparing oxidized asphalt;
[0009] S2, mixing and grinding the oxidized asphalt and the hard carbon precursor in step S1 to obtain a mixture, and cross-linking the mixture at 180-350° C. to obtain a composite material;
[0010] S3, calcining the composite material obtained in step S2 at 700-1400° C. to obtain a negative electrode material for a sodium ion battery.
[0011] Preferably, in step S2, the mass ratio of the oxidized asphalt to the hard carbon precursor is 100:20-20:100.
[0012] Preferably, in step S2, the cross-linking treatment time is 0.5-5h.
[0013] Preferably, in step S3, the calcination time is 2-8 hours.
[0014] Preferably, in step S2, the hard carbon precursor is one or more of chitin, chitosan and lignin.
[0015] Preferably, in step S1, the oxidized asphalt is obtained by oxidation treatment of asphalt, and the asphalt is one or more of petroleum asphalt, coal tar asphalt, and ethylene tar asphalt.
[0016] Preferably, in step S1, the oxidized asphalt is prepared by the following method: crushing and sieving the asphalt to obtain asphalt powder with a particle size of 1-75 μm; mixing the asphalt powder with a strong oxidizing acid, treating it at 70-90°C for 5-10 hours, and filtering and drying it to obtain acid-oxidized asphalt.
[0017] Preferably, in step S2, the cross-linking treatment is carried out in a protective gas atmosphere, and the protective gas is one or more of argon, nitrogen and helium.
[0018] On the other hand, the sodium ion battery negative electrode material prepared by the method for preparing the sodium ion battery negative electrode material provided by the present invention can be further prepared into a sodium ion battery.
[0019] The beneficial effects of the present invention are:
[0020] 1. The preparation method of the negative electrode material of a sodium ion battery provided by the present invention is to use oxidized asphalt as a soft carbon material and hydroxyl-rich biomass (chitin, chitosan and lignin) as a hard carbon precursor, mix the two, and then crosslink and carbonize to obtain the negative electrode material of a sodium ion battery. In the above process, not only can the performance advantages of soft carbon and hard carbon be fully utilized to improve the conductivity of the negative electrode material, improve the specific capacity and the first coulomb efficiency of the material, so that it exhibits superior energy storage capacity in the sodium ion battery, but also the strengthening of the crosslinking effect of soft carbon and hard carbon precursors can be utilized to inhibit the molecular interaction of aromatic hydrocarbons in the asphalt and the graphitization degree of soft carbon during the carbonization process. Through the above technical scheme, a negative electrode material for a sodium ion battery with high conductivity, specific capacity, rate performance and stability is obtained.
[0021] 2. The preparation method of the negative electrode material for a sodium ion battery provided by the present invention adjusts the ratio of soft carbon to hard carbon and optimizes the cross-linking conditions to increase the degree of cross-linking between soft and hard carbon and promote the formation of a more stable cross-linked structure. The emergence of the cross-linked structure can effectively improve the specific capacity and rate performance of the negative electrode material, enhance its rapid charge and discharge capabilities at high rates, enable it to meet the needs of fast charging, and expand its applicability in high-power applications. It has broad application prospects in the fields of electric vehicles, energy storage systems, etc.
[0022] 3. The sodium ion battery negative electrode material provided by the present invention adopts lignin and asphalt which are widely available and low in cost as raw materials, and can be prepared by only cross-linking and carbonization, which is conducive to mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the infrared spectrum of the sample after cross-linking and oxidation of the acid-oxidized asphalt and chitin prepared in Example 1;
[0024] Figure 2 This is the first charge and discharge curve of the sodium ion battery negative electrode material prepared in Example 1;
[0025] Figure 3 This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Example 1;
[0026] Figure 4 This is a cycle performance diagram of the sodium ion battery negative electrode material prepared in Example 1;
[0027] Figure 5 This is the first charge and discharge curve of the sodium ion battery negative electrode material prepared in Example 2;
[0028] Figure 6This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Example 2;
[0029] Figure 7 This is the first charge and discharge curve of the sodium ion battery negative electrode material prepared in Example 3;
[0030] Figure 8 This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Example 3;
[0031] Fig. 9 The XRD patterns of the samples prepared in Example 1 and Comparative Example 1 are shown in FIG.
[0032] Fig.10 This is the first charge and discharge curve of the sodium ion battery negative electrode material prepared in Comparative Example 1;
[0033] Fig.11 This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Comparative Example 1;
[0034] Fig.12 This is the first charge and discharge curve of the sodium ion battery negative electrode material prepared in Comparative Example 2;
[0035] Fig.13 This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Comparative Example 2;
[0036] Fig.14 This is the first charge and discharge curve of the sodium ion battery negative electrode material prepared in Comparative Example 3;
[0037] Fig.15 This is a rate performance diagram of the sodium ion battery negative electrode material prepared in Comparative Example 3. DETAILED DESCRIPTION
[0038] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is described in detail below with reference to the accompanying drawings and specific embodiments.
[0039] It should also be noted that, in order to avoid obscuring the present invention due to unnecessary details, only structures and / or processing steps closely related to the scheme of the present invention are shown in the drawings, while other details that are not closely related to the present invention are omitted.
[0040] In addition, it should be noted that the terms "comprises", "includes" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process, method, article or apparatus that includes a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or apparatus.
[0041] On the one hand, the present invention provides a sodium ion battery negative electrode material, which is prepared by mixing oxidized asphalt and a hard carbon precursor, and then subjecting the mixture to cross-linking treatment and calcination treatment.
[0042] On the other hand, the present invention also provides a method for preparing the above-mentioned sodium ion battery negative electrode material, which specifically comprises the following steps:
[0043] S1. preparing oxidized asphalt;
[0044] S2, mixing and grinding the oxidized asphalt in step S1 with the hard carbon precursor to obtain a mixture, and then cross-linking the mixture at 180-350° C. for 0.5-5 h to obtain a composite material;
[0045] S3. calcining the composite material obtained in step S2 at 700-1400° C. to obtain a negative electrode material for a sodium ion battery.
[0046] As an embodiment of the present invention, in step S1, the oxidized asphalt is prepared by the following method: crushing and sieving the asphalt to obtain an asphalt powder with a particle size of 1-75 μm; mixing the asphalt powder with a strong oxidizing acid, treating at 70-90° C. for 5-10 hours, and then filtering and drying to obtain acid-oxidized asphalt. Furthermore, the strong oxidizing acid is a mixture of concentrated HNO3 and concentrated H2SO4, and the volume ratio of the two is 3:7.
[0047] As an embodiment of the present invention, in step S2, the mass ratio of oxidized asphalt and hard carbon precursor is 100:20-20:100. When the mass ratio of the hard carbon precursor is too low, the degree of crosslinking cannot be guaranteed, and the proportion of hard carbon in the prepared negative electrode material is too low. When it is used as the negative electrode of a sodium ion battery, the specific capacity, rate performance and cycle stability are reduced; on the contrary, when the mass ratio of the hard carbon precursor is too high, the first coulombic efficiency of the prepared negative electrode material is reduced. Among them, the hard carbon precursor is one or more of chitin, chitosan and lignin; the asphalt is one or more of petroleum asphalt, coal tar asphalt, and ethylene tar asphalt.
[0048] As an embodiment of the present invention, in step S2, the cross-linking treatment is performed in a protective gas atmosphere, and the protective gas includes one or more of argon, nitrogen, and helium.
[0049] As an embodiment of the present invention, in step S3, the heating rate of the calcination process is 5°C / min, and the calcination time is 2-8h. Further, the calcination process is carried out in a protective gas atmosphere, and the protective gas includes one or more of argon, nitrogen, and helium.
[0050] The following is a further description of the sodium ion battery negative electrode material and preparation method thereof and the sodium ion battery proposed by the present invention in conjunction with specific embodiments:
[0051] Example 1
[0052] This embodiment prepares a sodium ion battery negative electrode material, and the specific preparation method includes the following steps:
[0053] S1. Weigh petroleum asphalt, crush and sieve it using a powder grinder to obtain asphalt powder with a particle size of less than 40 μm; mix the asphalt powder with a mixture of concentrated HNO3 and concentrated H2SO4 (V 浓HNO3 :V 浓H2SO4 =3:7) after treating at 80°C for 8h, filtering and drying to obtain oxidized asphalt;
[0054] S2, mixing oxidized asphalt and chitosan in a mass ratio of 1:1, grinding them evenly, placing them in a tube furnace, heating them to 300° C. under argon protection, and reacting them for 2 hours to obtain a cross-linked composite material;
[0055] S3, calcining the obtained cross-linked composite material in a tube furnace at 1200°C for 2h under argon protection, heating the temperature from room temperature to 1200°C at a heating rate of 5°C / min during the calcination process, and obtaining a negative electrode material for a sodium ion battery after cooling. It should be noted that, unless otherwise specified, the reagents used in the embodiments of the present invention can be purchased from the market.
[0056] The infrared spectrum of the negative electrode material is as follows Figure 1 As shown, compared with the negative electrode material made from unoxidized asphalt, the peak intensity of oxygen-containing functional groups, especially carboxylic acid ester group (-OC=O) and ether bond (COC) is significantly enhanced, indicating that the acid-oxidized asphalt and chitin have a stronger cross-linking effect. Further, in order to explore the application performance of the sodium ion battery negative electrode material prepared in this example in sodium ion batteries, the sodium ion battery negative electrode material is used as the sodium ion battery negative electrode active material, and is mixed with conductive carbon black and PVDF binder in a mass ratio of 8:1:1 to form a slurry and a negative electrode sheet, and a glass fiber membrane is used as a separator, a sodium sheet is used as a counter electrode, and 1 mol / L NaPF6 dimethyl glycol ether (DME) is used as an electrolyte to assemble a 2032 button battery, and the following tests are performed:
[0057] First charge and discharge performance test: 0.02A g -1 ; Test results such as Figure 2 As shown;
[0058] Rate performance test: 0.02, 0.05, 0.1, 0.2, 0.5, 1, 2, 5, 1A g -1 ; Test results such as Figure 3 As shown;
[0059] Cycle performance test: 1A g -1 ; Test results such as Figure 4 As shown;
[0060] Example 2
[0061] This embodiment prepares a sodium ion battery negative electrode material, and the specific preparation method includes the following steps:
[0062] S1. Weigh petroleum asphalt, crush and sieve it using a powder grinder to obtain asphalt powder with a particle size of less than 50 μm; mix the asphalt powder with a mixture of concentrated HNO3 and concentrated H2SO4 (V 浓HNO3 :V 浓H2SO4 =3:7) after treating at 80°C for 6h, filtering and drying to obtain oxidized asphalt;
[0063] S2, mixing oxidized asphalt and chitosan in a mass ratio of 2:1, grinding them evenly, placing them in a tube furnace, heating them to 300° C. under argon protection, and reacting them for 3 hours to obtain a cross-linked composite material;
[0064] S3. The obtained cross-linked composite material is calcined in a tubular furnace at 1200° C. for 2 h under argon protection. The temperature is increased from room temperature to 1200° C. at a heating rate of 5° C. / min during the calcination process. After cooling, a negative electrode material for a sodium ion battery is obtained.
[0065] Furthermore, in order to explore the application performance of the sodium ion battery negative electrode material prepared in this embodiment in sodium ion batteries, the sodium ion battery negative electrode material was used as the sodium ion battery negative electrode active material, and was mixed with conductive carbon black and PVDF binder in a mass ratio of 8:1:1 to form a slurry and made into a negative electrode sheet, and a glass fiber membrane was used as a separator, a sodium sheet was used as a counter electrode, and 1 mol / LNaPF6 dimethyl glycol ether (DME) was used as an electrolyte to assemble a 2032 type button battery. The first charge and discharge curve is shown in FIG. Figure 5 As shown in the figure, the rate performance diagram is as follows Figure 6 shown.
[0066] Example 3
[0067] This embodiment prepares a sodium ion battery negative electrode material, and the specific preparation method includes the following steps:
[0068] S1. Weigh ethylene tar asphalt, crush and sieve it using a powdering machine to obtain asphalt powder with a particle size of less than 40 μm; mix the asphalt powder with a mixture of concentrated HNO3 and concentrated H2SO4 (V 浓HNO3 :V 浓H2SO4 =3:7) after treating at 70°C for 6h, filtering and drying to obtain oxidized asphalt;
[0069] S2, mixing oxidized asphalt and chitosan in a mass ratio of 1:1, grinding them evenly, placing them in a tube furnace, heating them to 280° C. under argon protection, and reacting them for 2 hours to obtain a cross-linked composite material;
[0070] S3. The obtained cross-linked composite material is calcined in a tubular furnace at 1000° C. for 2 h under argon protection. The temperature is increased from room temperature to 1000° C. at a heating rate of 5° C. / min during the calcination process. After cooling, a negative electrode material for a sodium ion battery is obtained.
[0071] Furthermore, in order to explore the application performance of the sodium ion battery negative electrode material prepared in this embodiment in sodium ion batteries, the sodium ion battery negative electrode material was used as the sodium ion battery negative electrode active material, and was mixed with conductive carbon black and PVDF binder in a mass ratio of 8:1:1 to form a slurry and made into a negative electrode sheet, and a glass fiber membrane was used as a separator, a sodium sheet was used as a counter electrode, and 1 mol / LNaPF6 dimethyl glycol ether (DME) was used as an electrolyte to assemble a 2032 type button battery. The first charge and discharge curve is shown in FIG. Figure 7 As shown in the figure, the rate performance diagram is as follows Figure 8 shown.
[0072] Example 4
[0073] This embodiment prepares a sodium ion battery negative electrode material, and the specific preparation method includes the following steps:
[0074] S1. Weigh coal tar, crush and sieve it using a powdering machine to obtain asphalt powder with a particle size of less than 50 μm; mix the asphalt powder with a mixture of concentrated HNO3 and concentrated H2SO4 (V 浓HNO3 :V 浓H2SO4 =3:7) after treating at 80°C for 9h, filtering and drying to obtain oxidized asphalt;
[0075] S2, mixing oxidized asphalt and chitosan in a mass ratio of 1:1, grinding them evenly, placing them in a tube furnace, heating them to 320° C. under argon protection, and reacting them for 2 hours to obtain a cross-linked composite material;
[0076] S3. The obtained cross-linked composite material is calcined in a tubular furnace at 1200° C. for 2 h under argon protection. The temperature is increased from room temperature to 1200° C. at a heating rate of 5° C. / min during the calcination process. After cooling, a negative electrode material for a sodium ion battery is obtained.
[0077] Furthermore, in order to explore the application performance of the sodium ion battery negative electrode material prepared in this embodiment in sodium ion batteries, the sodium ion battery negative electrode material was used as the sodium ion battery negative electrode active material, mixed with conductive carbon black and PVDF binder in a mass ratio of 8:1:1 into a slurry and made into a negative electrode sheet, and assembled into a 2032 type button battery using a glass fiber membrane as a diaphragm, a sodium sheet as a counter electrode, and 1 mol / LNaPF6 of ethylene glycol dimethyl ether (DME) as an electrolyte.
[0078] Comparative Example 1
[0079] The difference between Comparative Example 1 and Example 1 is that in step S2, oxidized asphalt and chitosan are not mixed, but only oxidized asphalt is used to prepare the composite material, and the mass of oxidized asphalt in this step is equal to the sum of the masses of oxidized asphalt and chitosan in Example 1. The other steps are the same as Example 1 and will not be repeated here. The XRD patterns of the negative electrode materials prepared in Comparative Example 1 and Example 1 are shown in FIG. Fig. 9 As shown in the figure, it can be seen that the (002) diffraction peak of the carbon material prepared by cross-linking carbonization of oxidized asphalt and chitin in Example 1 is significantly weakened compared with that of Comparative Example 1, indicating that the cross-linking carbonization process of oxidized asphalt and chitin reduces the orderliness of the carbon structure of the material, thereby significantly reducing the graphitization degree of the carbon. This reduced graphitization degree may lead to higher rate performance and good cycle stability of the carbon material in terms of electrochemical performance. The first charge and discharge curve of the negative electrode material prepared under the above conditions is as follows Fig.10 As shown in the figure, it can be seen that at a current density of 0.02Ag-1, the specific capacity of the negative electrode material prepared in Comparative Example 1 is 254mAhg -1 , which is significantly lower than the negative electrode material prepared in Example 1 (318 mAh g -1 ). In addition, the first coulombic efficiency of the comparative strength (59%) is also significantly lower than that of Example 1 (72%). Fig.11 As shown in the figure, it can be seen that the specific capacity of the negative electrode material prepared in Comparative Example 1 at different current densities is significantly lower than that of Example 1. This difference shows that the material obtained by cross-linking and carbonizing oxidized asphalt and chitin exhibits higher capacity retention and better electrochemical activity in the initial cycle.
[0080] Comparative Example 2
[0081] The difference between Comparative Example 2 and Example 1 is that in step S2, the oxidized asphalt and chitosan are not mixed, but only chitosan is used to prepare the composite material, and the mass of chitosan in this step is equal to the sum of the masses of oxidized asphalt and chitosan in Example 1. The other steps are the same as those in Example 1 and will not be repeated here. The first charge and discharge curve of the negative electrode material obtained under the above conditions is as follows: Fig.12 As shown in the figure, it can be seen that the reversible capacity of the negative electrode material prepared in Comparative Example 2 is only 197 mAh g -1 , and the first coulombic efficiency is less than 70%; the rate performance diagram is as follows Fig.13 As shown in the figure, it can be seen that the specific capacity of the negative electrode material prepared in Comparative Example 2 at different current densities is significantly lower than that of Example 1.
[0082] Comparative Example 3
[0083] The difference between Comparative Example 3 and Example 1 is that the oxidized asphalt and chitin are directly carbonized without the crosslinking treatment in step S2. The other steps are the same as those in Example 1 and will not be described again. The first charge and discharge curve of the negative electrode material obtained under the above conditions is as follows: Fig.14 As shown in the figure, it can be seen that the reversible capacity of the negative electrode material prepared in Comparative Example 3 is only 176 mAhg -1 , and the first coulombic efficiency is only 55%; the rate performance diagram is as follows Fig.15 As shown in the figure, it can be seen that the specific capacity of the negative electrode material prepared in Comparative Example 3 at different current densities is significantly lower than that of Example 1.
[0084] The above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention.
Claims
1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The steps include: S1. preparing oxidized asphalt; S2, mixing and grinding the oxidized asphalt and the hard carbon precursor in step S1 to obtain a mixture, and cross-linking the mixture at 180-350° C. to obtain a composite material; S3, calcining the composite material obtained in step S2 at 700-1400° C. to obtain a negative electrode material for a sodium ion battery.
2. The preparation method according to claim 1, characterized in that: In step S2, the mass ratio of the oxidized asphalt to the hard carbon precursor is 100:20-20:
100.
3. The preparation method according to claim 1, characterized in that: In step S2, the cross-linking treatment time is 0.5-5 hours.
4. The preparation method according to claim 1, characterized in that: In step S3, the calcination time is 2-8 hours.
5. The preparation method according to claim 1 or 2, characterized in that: In step S2, the hard carbon precursor is one or more of chitin, chitosan and lignin.
6. The preparation method according to claim 1, characterized in that: In step S1, the oxidized asphalt is obtained by oxidation treatment of asphalt, and the asphalt is one or more of petroleum asphalt, coal tar asphalt, and ethylene tar asphalt.
7. The preparation method according to claim 6, characterized in that: In step S1, the oxidized asphalt is prepared by the following method: crushing and sieving the asphalt to obtain asphalt powder with a particle size of 1-75 μm; mixing the asphalt powder with a strong oxidizing acid, treating it at 70-90° C. for 5-10 hours, and filtering and drying it to obtain acid-oxidized asphalt.
8. The preparation method according to claim 1, characterized in that: In step S2, the cross-linking treatment is carried out in a protective gas atmosphere, wherein the protective gas is one or more of argon, nitrogen, and helium.
9. A sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 8.
10. A sodium ion battery, characterized in that: Including the sodium ion battery negative electrode material according to claim 9.
Citation Information
Cited By
Soft carbon and hard carbon co-coated nanometer silicon negative electrode material and preparation method thereof
CN121076094A
Soft carbon and hard carbon co-coated nano-silicon negative electrode material and preparation method thereof
CN121076094B
Asphalt-based hard carbon negative electrode material, preparation method and application thereof, and sodium ion battery
CN122704889A